Kebocoran Tepi Restorasi Resin Komposit Setelah Aplikasi Pasta Buah Stroberi Sebagai Bahan Bleaching - Evi Veronica Chandra; Sri Yogyarti; Titien Hary Agustantina (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2012)
The influence of strawberry paste as bleaching alternative material toward microleakage of composite resin restoration of the teeth is still unknown so that a research should be conducted. To qualitily assess the effects of bleaching with blended strawberry paste on restorated teeth by performing scoring of microleakage analysis. Four group of sample i.e. group 1: ten restorated teeth soaked in saline for two weeks, group 2 : ten restorated teeth soaked in blended strawberry paste for 5 minutes every 8 hours for two weeks, group 3 : ten restorated teeth soaked in saline for three weeks, group 4 : ten restorated teeth soaked in blended strawberry paste for 5 minutes every 8 hours for three weeks. Each group was stroraged in incubator 37 degrees celcius. Then microleakage was observed with digital microscope. Penetration of methylen blue was scored on a scale of 0 to 4 applied in every sample. The data was analyzed with Kruskal – Wallis Test and Mann – Whitney Test. There was a significant differences of group 1 and group 4, group 2 and group 4, group 3 and group 4. The application of blended strawberry paste in two weeks and three weeks causes microleakage of composite resin restoration while in three weeks the microleakage significantly deeper than two